(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
The cost of producing sanitary ware in Bangladesh is substantially low as compared to the advanced countries, because of low labour cost and abundance of basic raw materials. Ten sanitary ware compositions were prepared using Bijoypur clay, black clay, red clay, ball clay and china clay with fluxes and filler materials. Chemical compositions of the raw materials and the formulated batch compositions were determined. Physical properties (linear shrinkage, bulk density, apparent porosity, water absorption etc) and the modulus of rupture (MOR) of the prepared body compositions were also determined. The sample specimens were fired at 1150°C and 1200°C. Compositions S-3, S-4, S- 5, S-7, S-8 and S-10 at 1150°C were found to be of good quality. Key words: Linear shrinkage; Bulk density; Water absorption; MOR; Red clay; Black clay. DOI: 10.3329/bjsir.v45i4.7386 Bangladesh J. Sci. Ind. Res. 45(4), 387-392, 2010